Предмет: Алгебра,
автор: NikonNikov
Найти производную функции y=(x²+1)(x³-3) при x=2
Ответы
Автор ответа:
4
f(x)=(x²+1)(x³-3)
f'(x)=2x*(x³-3)+3x²*(x²+1) = 2x⁴ - 6x + 3x⁴ + 3x² = 5x⁴+3x²-6x
f'(x)=2x*(x³-3)+3x²*(x²+1) = 2x⁴ - 6x + 3x⁴ + 3x² = 5x⁴+3x²-6x
Аnuta:
f'(2)=5*2⁴+3*2²-6*2=80+12-12=80
Похожие вопросы
Предмет: Английский язык,
автор: anutka758o
Предмет: Русский язык,
автор: baybekovam
Предмет: Русский язык,
автор: devo4ka374
Предмет: Математика,
автор: akipo
Предмет: Информатика,
автор: german1661